Risk assessment in sustainable food supply chains: A holistic approach by using HOR-SWOT-ANP/AHP to ensuring performance improvement - Prima Dania, Wike Agustin; Lu’ayya, Naila Maulidina; Septifani, Riska (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The global food supply chain plays an essential role in economic development while addressing environmental and social issues in its business system. However, this complex network is exposed to various risk factors related to sustainability that can disrupt the supply chain performance. CV. XYZ is a food manufacturer that produces jackfruit chips in Indonesia. During the supply chain process, this company needs to manage the various risks across the supplier, manufacturer, and retailer stages. By identifying and evaluating risks at each stage, mitigation and improvement strategies can be proposed. Therefore, this research aimed to analyze the supply chain risk mitigation and performance improvement strategies for maintaining supply chain stability and performance. House of Risk (HOR) was applied to analyze the mitigation strategies, while SWOT with analytical networking process (ANP) or analytical hierarchy process (AHP)/ (i.e., SWOT-ANP/AHP method)was used for analyzing performance improvement strategies by considering the weight of each factor. The result shows that twelve mitigation strategies are needed to mitigate the fourteen risk agents that focus on improving production activities and human resources. Moreover, eleven strategies have been proposed to improve sustainable supply chain performance in the future, focusing more on marketing activities and enhancing human resource capabilities.